Ephedra yangthangensis (Ephedraceae), a new species from Himachal Pradesh, India (Bangladesh Journal of Plant Taxonomy, 2016)
A new species Ephedra yangthangensis Prabha Sharma & Rita Singh is described, and illustrated from Himachal Pradesh, India. This new species is most similar to E. intermedia Schr. & Meyer, from which it is distinguishable by its smaller male strobili, shorter length and curved synangiophore, yellowish orange fleshy bracts of bigger female strobili, fade orange scale leaves and light green robust stem as compared to the other flourishing species E. intermedia.Bangladesh J. Plant Taxon. 23(2): 195-198, 2016 (December)